2020
DOI: 10.12669/pjms.36.3.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cranial CT scan evaluation of morphological variations and location of pterion in Pakistani male population for lateral neurosurgical approach

Abstract: Objective: To determine the morphological variations and location of pterion in Pakistani male population. Methods: This retrospective observational study was carried out in the Department of Radiology, Shifa International Hospital from December 2018 to June 2019. The sample size was calculated by Open Epi web-based calculator. Fifty-three cranial CT scans with slice thickness of 0.5mm; consecutive scans of males were randomly selected. The patients with no craniofacial fracture and ages from 25 to 45 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Kalthur et al 13 found the distance between the center of pterion and behind the frontozygomatic suture as 3.27 ± 0.06 cm in Indian skulls in 2017. In the study of Rafi et al 38 conducted on 53 cranial computed tomography, they reported the location of pterion as it lied 2.230 ± 0.227 cm posterior of the zygomatic suture in the right side and 2.275 ± 0.253 cm on the left side. We found the distance between pterion and frontozygomatic suture as 33.73 ± 3.61 mm on the right side and 35.85 ± 6.39 mm on the left side.…”
Section: Discussionmentioning
confidence: 99%
“…Kalthur et al 13 found the distance between the center of pterion and behind the frontozygomatic suture as 3.27 ± 0.06 cm in Indian skulls in 2017. In the study of Rafi et al 38 conducted on 53 cranial computed tomography, they reported the location of pterion as it lied 2.230 ± 0.227 cm posterior of the zygomatic suture in the right side and 2.275 ± 0.253 cm on the left side. We found the distance between pterion and frontozygomatic suture as 33.73 ± 3.61 mm on the right side and 35.85 ± 6.39 mm on the left side.…”
Section: Discussionmentioning
confidence: 99%
“… 15 This necessitates that neurosurgeons and radiologists should know the presence and incidence of these structures in general and in their local population in particular. 8 9 …”
Section: Discussionmentioning
confidence: 99%
“…Forensic scientists and anthropologists also use pterion as an anterolateral landmark to determine the age of skeletal remains. 8 9 Based on the articulation of constituent bones, researchers have classified the pterion into various types. The most commonly used classification is the one coined by Murphy in 1956, describes four types of the pterion: (i) sphenoparietal (SP), (ii) frontotemporal (FT), (iii) stellate (S), and (iv) epipteric (E).…”
Section: Introductionmentioning
confidence: 99%